Access to financial services and innovation: firm-level data for Ethiopia. Issue 1 (2nd January 2021) - Regasa, Dereje Getachew; Diro, Bekele Abraham; Tadesse, Ephrem Dejene; Buta, Meseret Niguse
ABSTRACT: Using World Bank's Ethiopian Enterprise Survey round of 2011 and 2015 data from Ethiopian manufacturing and service ﬁrms, this paper identiﬁes the effect of financial services on the innovation strategies of firms. We find a strong positive correlation between firm's access to external finance and its innovative activities. Our preferred specification, the instrumental variable estimator, suggests that a 1% rise in external financing source in the firm's total fund increases the propensity to innovate the firm's operation by about 2%. In a similar spirit, credit-constrained firms have about 24% lower incidence of innovation compared to credit unconstrained firms. We find that the results are substantially robust across alternative econometric specification. The results also remain consistent for the individual components of innovation index such as product, process, organizational, marketing and R&D innovation activities.